Theory of phase transitions : rigorous results - Sinai, IA. G. (IAkov Grigorevich), 1935- (International series in natural philosophy, 1982)
Theory of Phase Transitions: Rigorous Results is inspired by lectures on mathematical problems of statistical physics presented in the Mathematical Institute of the Hungarian Academy of Sciences, Budapest. The aim of the book is to expound a series of rigorous results about the theory of phase transitions.